Prevention and cure of rock burst on the mining face in the stress concentration area of the residual coal pillar - Xiaoming Tang; Feng Ju; Anye Cao (Discover Applied Sciences)
Abstract Coal mining in China has extended to greater depths, making the urgent resolution of associated rock burst issues a critical priority. The retention of coal pillars often leads to the formation of stress concentration zones, increasing the rock burst hazard on lower coal seams and posing challenges to the safe production of coal mines. Using the 8332 working face of Xuzhuang Mine as an example, this paper investigates the factors influencing the rock burst hazard of the working face under the residual coal pillar in the goaf, as well as the evolution of the overburden structure and the stress distribution characteristics during the mining process. Based on the microseismic data collected during mining, the spatio-temporal evolution of microseismic activity in the working face under the residual coal pillar in the goaf is analyzed. The results show that: the ‘F’ and ‘T’ spatial structures are determined as the critical stress concentration zone. A high rock burst hazard in the affected area of the residual coal pillar. During the mining period, microseismic energy and frequency are generally low, exhibiting a trend of first increasing, then decreasing, and finally increasing again. A prevention strategy for rock bursts in the 8332 working face was developed based on its impact characteristics. Its feasibility and effectiveness were verified, providing theoretical support and technical guidance for mining under similar conditions. The findings of this study provide valuable insights for developing effective rock burst prevention strategies in deep coal mines, thereby enhancing mining safety and efficiency.